Structural Analysis of a Main Construction Assemblies of the New Wagon Prototype Type Zans - Šťastniak, Pavol; Smetanka, Lukáš; Moravčík, Marián (Manufacturing Technology Journal, 2018)
The paper is part of the publication series, which describe the most significant and innovative research and development design solutions and computational procedures as part of European structural funds project. The object of this article is strength conditions assessment of a new structure of railway tank wagon. For validation of the new construction assemblies, there has been created a substitute simulation model. Results of calculations and prototype tests prove, that new structure of the construction satisfies strength assessments according to valid requirements and standards.
Keywords: tank wagon; structural analysis; computer simulation